2020
DOI: 10.1371/journal.pone.0235048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antithrombotic stewardship on the efficacy and safety of antithrombotic therapy during and after hospitalization

Abstract: Background Although the benefits of antithrombotic drugs are indisputable to reduce thrombotic events, they carry a high risk of compromising patient safety. No previous studies investigated the implementation and (cost-) effectiveness of a hospital-based multidisciplinary antithrombotic team on bleeding and thrombotic outcomes. The primary aim of this study was to compare the proportion of patients with a composite end point consisting of one or more bleeding episodes or one or more thrombotic event from hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…In addition, a study of Dreijer et al . conducted in patients using anticoagulants showed that implementation of a multidisciplinary antithrombotic team over time significantly reduces adverse drug reactions such as bleedings or thrombotic events from hospitalization until 3 months after hospitalization and resulted in a lower all‐cause mortality 43 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study of Dreijer et al . conducted in patients using anticoagulants showed that implementation of a multidisciplinary antithrombotic team over time significantly reduces adverse drug reactions such as bleedings or thrombotic events from hospitalization until 3 months after hospitalization and resulted in a lower all‐cause mortality 43 …”
Section: Discussionmentioning
confidence: 99%
“…Also with DOACs, DDIs still need to be considered and data on clinical relevance of these DDIs are often lacking. Hospital pharmacists may possibly be more aware of these concerns since they are often involved in clinical pharmacy activities and antithrombotic stewardship programmes 26,27 . Such programmes are currently lacking in primary care in Belgium, which may explain the difference in perception between hospital and community pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] The S-team study recently showed that implementation of hospital-based anticoagulant stewardship programmes had a significant impact on bleeding and thrombotic events and resulted in lower all-cause mortality. 12 Also, pharmacistled clinical services including reviewing all orders for NOACs can reduce the number of inappropriate prescriptions of these drugs. [13][14][15][16] Such interventions are, however, time and personnel intensive, limiting their efficacy to change hospital-wide prescribing behaviours.…”
Section: Introductionmentioning
confidence: 99%